An admixture scan in 1,484 African American women with breast cancer - Fejerman, Laura (2009)
African American women with breast cancer present more commonly with aggressive tumors that do not express the estrogen receptor (ER) and progesterone receptor (PR) compared with European American women. Whether this disparity is the result of inherited factors has not been established. We performed an admixture-based genome-wide scan to search for risk alleles for breast cancer that are highly differentiated in frequency between African American and European American women and may contribute to specific breast cancer phenotypes, such as ER negative (ER−) disease. African American women with invasive breast cancer (n=1,484) were pooled from 6 population-based studies and typed at ~1,500 ancestry informative markers (AIMs). We investigated global genetic ancestry and performed a whole genome admixture scan searching for breast cancer predisposing loci in association with disease phenotypes. We found a significant difference in ancestry between ER+PR+ and ER−PR− women, with higher European ancestry among ER+PR+ individuals, after controlling for possible confounders (OR for a 0 to 1 change in European ancestry proportion=2.84, 95% CI: 1.13–7.14, p=0.026). Women with localized tumors had higher European ancestry than women with non-localized tumors (OR=2.65, CI: 1.11–6.35, p=0.029). No genome-wide statistically significant associations were observed between European or African ancestry at any specific locus and breast cancer, or in analyses stratified by ER/PR status, stage or grade. In summary, in African American women genetic ancestry is associated with ER/PR status and disease stage. However, we found little evidence that genetic ancestry at any one region contributes significantly to breast cancer risk or hormone receptor status.